Reliable electrocortical dynamics of target-directed pass-kicks - Piskin, Daghan Yuksel; Büchel, Daniel; Lehmann, Tim; Baumeister, Jochen (Cognitive Neurodynamics)
Abstract Football is one of the most played sports in the world and kicking with adequate accuracy increases the likelihood of winning a competition. Although studies with different target-directed movements underline the role of distinctive cortical activity on superior accuracy, little is known about cortical dynamics associated with kicking. Mobile electroencephalography is a popular tool to investigate cortical modulations during movement, however, inherent and artefact-related pitfalls may obscure the reliability of functional sources and their activity. The purpose of this study was therefore to describe consistent cortical dynamics underlying target-directed pass-kicks based on test–retest reliability estimates. Eleven participants performed a target-directed kicking task at two different sessions within one week. Electroencephalography was recorded using a 65-channel mobile system and behavioural data were collected including motion range, acceleration and accuracy performance. Functional sources were identified using independent component analysis and clustered in two steps with the components of first and subsequently both sessions. Reliability estimates of event-related spectral perturbations were computed pixel-wise for participants contributing with components of both sessions. The parieto-occipital and frontal clusters were reproducible for the same majority of the sample at both sessions. Their activity showed consistent alpha desyhronization and theta sychnronisation patterns with substantial reliability estimates revealing visual and attentional demands in different phases of kicking. The findings of our study reveal prominent cortical demands during the execution of a target-directed kick which may be considered in practical implementations and provide promising academic prospects in the comprehension and investigation of cortical activity associated with target-directed movements.
Keywords: Exercise Neuroscience

The Mode of Endurance Exercise Influences Changes in EEG Resting State Graphs among High-Level Cross-Country Skiers - Büchel, Daniel; Torvik, Per Øyvind; Lehmann, Tim; Sandbakk, Øyvind; Baumeister, Jochen (Medicine & Science in Sports & Exercise)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

The Mode of Endurance Exercise Influences Changes in EEG Resting State Graphs among High-Level Cross-Country Skiers. - Büchel, Daniel; Torvik, PØ; Lehmann, Tim; Sandbakk, Ø; Baumeister, Jochen (Med Sci Sports Exerc)

Mobile Electroencephalography Reveals Differences in Cortical Processing During Exercises With Lower and Higher Cognitive Demands in Preadolescent Children - Becker, Linda; Büchel, Daniel; Lehmann, Tim; Kehne, Miriam; Baumeister, Jochen (Pediatric Exercise Science)
Purpose : The aim of this study was to examine whether cortical activity changes during exercise with increasing cognitive demands in preadolescent children. Method : Twenty healthy children (8.75 [0.91] y) performed one movement game, which was conducted with lower and higher cognitive demands. During a baseline measurement and both exercise conditions, cortical activity was recorded using a 64-channel electroencephalographic system, and heart rate was assessed. Ratings of perceived excertion and perceived cognitive engagement were examined after each condition. To analyze power spectral density in the theta, alpha-1, and alpha-2 frequency bands, an adaptive mixture independent component analysis was used to determine the spatiotemporal sources of cortical activity, and brain components were clustered to identify spatial clusters. Results : One-way repeated-measures analyses of variance revealed significant main effects for condition on theta in the prefrontal cluster, on alpha-1 in the prefrontal, central, bilateral motor, bilateral parieto-occipital, and occipital clusters, and on alpha-2 in the left motor, central, and left parieto-occipital clusters. Compared with the lower cognitive demand exercise, cortical activity was significantly higher in theta power in the prefrontal cluster and in alpha-1 power in the occipital cluster during the higher cognitive demand exercise. Conclusion : The present study shows that exercise complexity seems to influence cortical processing as it increased with increasing cognitive demands.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine; Pediatrics; Perinatology and Child Health

A Comparison of the Most Intense Periods (MIPs) During Competitive Matches and Training Over an 8-Week Period in a Male Elite Field Hockey Team - Büchel, Daniel; Döring, Michael; Baumeister, Jochen (Journal of Science in Sport and Exercise)
Abstract Purpose Wearables serve to quantify the on-court activity in intermittent sports such as field hockey (FH). Based on objective data, benchmarks can be determined to tailor training intensity and volume. Next to average and accumulated values, the most intense periods (MIPs) during competitive FH matches are of special interest, since these quantify the peak intensities players experience throughout the intermittent matches. The aim of this study was to retrospectively compare peak intensities between training and competition sessions in a male FH team competing in the first german division. Methods Throughout an 8-week in-season period, 372 individual activity datasets (144 datasets from competitive sessions) were recorded using the Polar Team Pro sensor (Kempele, Finland). MIPs were calculated applying a rolling window approach with predefined window length (1–5 min) and calculated for Total distance, High-Intensity-Running distance (> 16 km/h), Sprinting distance (> 20 km/h) and Acceleration load. Significant differences between training and competition MIPs were analysed through non-parametric statistical tests ( P < 0.05). Results Analyses revealed higher MIPs during competition for all considered outcomes ( P < 0.001). Effect size estimation revealed strongest effects for sprinting distance ( d = 1.89 to d = 1.22) and lowest effect sizes for acceleration load ( d = 0.92 to d = 0.49). Conclusion The present findings demonstrate that peak intensities during training do not reach those experienced during competitive sessions in a male FH team. Training routines such as manipulations of court-dimensions and team sizes might contribute to this discrepancy. Coaches should compare training and competition intensities to recalibrate training routines to optimize athletes’ preparation for competition.
Keywords: Nutrition and Dietetics; Rehabilitation; Orthopedics and Sports Medicine; Physical Therapy; Sports Therapy and Rehabilitation; Physiology

Increased Cognitive Demands Affect Agility Performance in Female Athletes - Implications for Testing and Training of Agility in Team Ball Sports - Büchel, Daniel; Gokeler, Alli; Heuvelmans, Pieter; Baumeister, Jochen (Perceptual and Motor Skills)
Agility, a key component of team ball sports, describes an athlete´s ability to move fast in response to changing environments. While agility requires basic cognitive functions like processing speed, it also requires more complex cognitive processes like working memory and inhibition. Yet, most agility tests restrict an assessment of cognitive processes to simple reactive times that lack ecological validity. Our aim in this study was to assess agility performance by means of total time on two agility tests with matched motor demands but with both low and high cognitive demands. We tested 22 female team athletes on SpeedCourt, using a simple agility test (SAT) that measured only processing speed and a complex agility test (CAT) that required working memory and inhibition. We found excellent to good reliability for both our SAT (ICC = .79) and CAT (ICC =.70). Lower agility performance on the CAT was associated with increased agility total time and split times ( p < .05). These results demonstrated that agility performance depends on the complexity of cognitive demands. There may be interference-effects between motor and cognitive performances, reducing speed when environmental information becomes more complex. Future studies should consider agility training models that implement complex cognitive stimuli to challenge athletes according to competitive demands. This will also allow scientists and practitioners to tailor tests to talent identification, performance development and injury rehabilitation.
Keywords: Sensory Systems; Experimental and Cognitive Psychology

Cortical responses to sport-specific stimuli in a standing stop signal task - Scharfen, Hans-Erik; Lehmann, Tim; Büchel, Daniel; Baumeister, Jochen (Psychology of Sport and Exercise)
Keywords: Applied Psychology

Ecological Validity in Exercise Neuroscience Research: A Systematic Investigation - Chang, M.; Büchel, Daniel; Reinecke, K.; Lehmann, T.; Baumeister, Jochen (European Journal of Neuroscience)
Keywords: General Neuroscience

Surface Instability Modulates Cortical Information Processing In Multi-Joint Compound Movements - Lehmann, Tim; Visser, Anton; Havers, Tim; Büchel, Daniel; Baumeister, Jochen (Medicine &Science in Sports& Exercise)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Changes In Eeg Microstate Patterns Following Exhaustive Treadmill Exercise When Employing Reduced Channel Resolution - Büchel, Daniel; Allen, Carlos; Lehmann, Tim; Sandbakk, Øyvind; Baumeister, Jochen (Medicine &Science in Sports& Exercise)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Continuous table tennis is associated with processing in frontal brain areas: an EEG approach - Visser, Anton; Büchel, Daniel; Lehmann, Tim; Baumeister, Jochen (Experimental Brain Research)
Abstract Coordinative challenging exercises in changing environments referred to as open-skill exercises seem to be beneficial on cognitive function. Although electroencephalographic research allows to investigate changes in cortical processing during movement, information about cortical dynamics during open-skill exercise is lacking. Therefore, the present study examines frontal brain activation during table tennis as an open-skill exercise compared to cycling exercise and a cognitive task. 21 healthy young adults conducted three blocks of table tennis, cycling and n-back task. Throughout the experiment, cortical activity was measured using 64-channel EEG system connected to a wireless amplifier. Cortical activity was analyzed calculating theta power (4–7.5 Hz) in frontocentral clusters revealed from independent component analysis. Repeated measures ANOVA was used to identify within subject differences between conditions (table tennis, cycling, n-back; p < .05). ANOVA revealed main-effects of condition on theta power in frontal ( p < .01, η p 2 = 0.35) and frontocentral ( p < .01, η p 2 = 0.39) brain areas. Post-hoc tests revealed increased theta power in table tennis compared to cycling in frontal brain areas ( p < .05, d = 1.42). In frontocentral brain areas, theta power was significant higher in table tennis compared to cycling ( p < .01, d = 1.03) and table tennis compared to the cognitive task ( p < .01, d = 1.06). Increases in theta power during continuous table tennis may reflect the increased demands in perception and processing of environmental stimuli during open-skill exercise. This study provides important insights that support the beneficial effect of open-skill exercise on brain function and suggest that using open-skill exercise may serve as an intervention to induce activation of the frontal cortex.
Keywords: General Neuroscience

Surface Instability Modulates Cortical Information Processing In Multi-Joint Compound Movements - Lehmann, Tim; Visser, Anton; Havers, Tim; Büchel, Daniel; Baumeister, Jochen (Medicine & Science in Sports & Exercise)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Effects of surface instability on cortical information processing during multi- joint compound movements: an exploratory EEG study - Lehmann, Tim; Visser, Anton; Havers, Tim; Büchel, Daniel; Baumeister, Jochen

Changes In Eeg Microstate Patterns Following Exhaustive Treadmill Exercise When Employing Reduced Channel Resolution - Büchel, Daniel; Allen, Carlos; Lehmann, Tim; Sandbakk, Øyvind; Baumeister, Jochen (Medicine & Science in Sports & Exercise)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Ecological validity in exercise neuroscience research: A systematic investigation - Chang, Melissa; Büchel, Daniel; Reinecke, Kirsten; Lehmann, Tim; Baumeister, Jochen (European Journal of Neuroscience)
Keywords: General Neuroscience

Exploring intensity-dependent modulations in EEG resting-state network efficiency induced by exercise - Büchel, Daniel; Sandbakk, Øyvind; Baumeister, Jochen (European Journal of Applied Physiology)
Abstract Purpose Exhaustive cardiovascular load can affect neural processing and is associated with decreases in sensorimotor performance. The purpose of this study was to explore intensity-dependent modulations in brain network efficiency in response to treadmill running assessed from resting-state electroencephalography (EEG) measures. Methods Sixteen trained participants were tested for individual peak oxygen uptake (VO 2 peak ) and performed an incremental treadmill exercise at 50% (10 min), 70% (10 min) and 90% speed VO 2 peak (all-out) followed by cool-down running and active recovery. Before the experiment and after each stage, borg scale (BS), blood lactate concentration (B La ), resting heartrate (HR rest ) and 64-channel EEG resting state were assessed. To analyze network efficiency, graph theory was applied to derive small world index (SWI) from EEG data in theta, alpha-1 and alpha-2 frequency bands. Results Analysis of variance for repeated measures revealed significant main effects for intensity on BS, B La , HR rest and SWI. While BS, B La and HR rest indicated maxima after all-out, SWI showed a reduction in the theta network after all-out. Conclusion Our explorative approach suggests intensity-dependent modulations of resting-state brain networks, since exhaustive exercise temporarily reduces brain network efficiency. Resting-state network assessment may prospectively play a role in training monitoring by displaying the readiness and efficiency of the central nervous system in different training situations.

Stance leg and surface stability modulate cortical activity during human single leg stance - Büchel, Daniel; Lehmann, Tim; Ullrich, Sarah; Cockcroft, John; Louw, Quinette; Baumeister, Jochen (Experimental Brain Research)
Abstract Mobile Electroencephalography (EEG) provides insights into cortical contributions to postural control. Although changes in theta (4–8 Hz) and alpha frequency power (8–12 Hz) were shown to reflect attentional and sensorimotor processing during balance tasks, information about the effect of stance leg on cortical processing related to postural control is lacking. Therefore, the aim was to examine patterns of cortical activity during single-leg stance with varying surface stability. EEG and force plate data from 21 healthy males (22.43 ± 2.23 years) was recorded during unipedal stance (left/right) on a stable and unstable surface. Using source-space analysis, power spectral density was analyzed in the theta, alpha-1 (8–10 Hz) and alpha-2 (10–12 Hz) frequency bands. Repeated measures ANOVA with the factors leg and surface stability revealed significant interaction effects in the left ( p = 0.045, η p 2 = 0.13) and right motor clusters ( F = 16.156; p = 0.001, η p 2 = 0.41). Furthermore, significant main effects for surface stability were observed for the fronto-central cluster (theta), left and right motor (alpha-1), as well as for the right parieto-occipital cluster (alpha-1/alpha-2). Leg dependent changes in alpha-2 power may indicate lateralized patterns of cortical processing in motor areas during single-leg stance. Future studies may therefore consider lateralized patterns of cortical activity for the interpretation of postural deficiencies in unilateral lower limb injuries.

Functional Cortical Connectivity Related to Postural Control in Patients Six Weeks After Anterior Cruciate Ligament Reconstruction - Lehmann, Tim; Büchel, Daniel; Mouton, Caroline; Gokeler, Alli; Seil, Romain; Baumeister, Jochen (Frontiers in Human Neuroscience)
Whereas initial findings have already identified cortical patterns accompanying proprioceptive deficiencies in patients after anterior cruciate ligament reconstruction (ACLR), little is known about compensatory sensorimotor mechanisms for re-establishing postural control. Therefore, the aim of the present study was to explore leg dependent patterns of cortical contributions to postural control in patients 6 weeks following ACLR. A total of 12 patients after ACLR (25.1 ± 3.2 years, 178.1 ± 9.7 cm, 77.5 ± 14.4 kg) and another 12 gender, age, and activity matched healthy controls participated in this study. All subjects performed 10 × 30 s. single leg stances on each leg, equipped with 64-channel mobile electroencephalography (EEG). Postural stability was quantified by area of sway and sway velocity. Estimations of the weighted phase lag index were conducted as a cortical measure of functional connectivity. The findings showed significant group × leg interactions for increased functional connectivity in the anterior cruciate ligament (ACL) injured leg, predominantly including fronto−parietal [ F (1, 22) = 8.41, p ≤ 0.008, η 2 = 0.28], fronto−occipital [ F (1, 22) = 4.43, p ≤ 0.047, η 2 = 0.17], parieto−motor [ F (1, 22) = 10.30, p ≤ 0.004, η 2 = 0.32], occipito−motor [ F (1, 22) = 5.21, p ≤ 0.032, η 2 = 0.19], and occipito−parietal [ F (1, 22) = 4.60, p ≤ 0.043, η 2 = 0.17] intra−hemispherical connections in the contralateral hemisphere and occipito−motor [ F (1, 22) = 7.33, p ≤ 0.013, η 2 = 0.25] on the ipsilateral hemisphere to the injured leg. Higher functional connectivity in patients after ACLR, attained by increased emphasis of functional connections incorporating the somatosensory and visual areas, may serve as a compensatory mechanism to control postural stability of the injured leg in the early phase of rehabilitation. These preliminary results may help to develop new neurophysiological assessments for detecting functional deficiencies after ACLR in the future.

EEG-derived brain graphs are reliable measures for exploring exercise-induced changes in brain networks - Büchel, Daniel; Lehmann, Tim; Sandbakk, Øyvind; Baumeister, Jochen (Scientific Reports)
Abstract The interaction of acute exercise and the central nervous system evokes increasing interest in interdisciplinary research fields of neuroscience. Novel approaches allow to monitor large-scale brain networks from mobile electroencephalography (EEG) applying graph theory, but it is yet uncertain whether brain graphs extracted after exercise are reliable. We therefore aimed to investigate brain graph reliability extracted from resting state EEG data before and after submaximal exercise twice within one week in male participants. To obtain graph measures, we extracted global small-world-index (SWI), clustering coefficient (CC) and characteristic path length (PL) based on weighted phase leg index (wPLI) and spectral coherence (Coh) calculation. For reliability analysis, Intraclass-Correlation-Coefficient (ICC) and Coefficient of Variation (CoV) were computed for graph measures before (REST) and after POST) exercise. Overall results revealed poor to excellent measures at PRE and good to excellent ICCs at POST in the theta, alpha-1 and alpha-2, beta-1 and beta-2 frequency band. Based on bootstrap-analysis, a positive effect of exercise on reliability of wPLI based measures was observed, while exercise induced a negative effect on reliability of Coh-based graph measures. Findings indicate that brain graphs are a reliable tool to analyze brain networks in exercise contexts, which might be related to the neuroregulating effect of exercise inducing functional connections within the connectome. Relative and absolute reliability demonstrated good to excellent reliability after exercise. Chosen graph measures may not only allow analysis of acute, but also longitudinal studies in exercise-scientific contexts.

Stance leg and surface stability modulate cortical activity during human single leg stance - Büchel, Daniel; Lehmann, Tim; Ullrich, Sarah; Cockcroft, John; Louw, Quinette; Baumeister, Jochen (Experimental Brain Research)

Functional Cortical Connectivity Related to Postural Control in Patients Six Weeks After Anterior Cruciate Ligament Reconstruction - Lehmann, Tim; Büchel, Daniel; Mouton, Caroline; Gokeler, Alli; Seil, Romain; Baumeister, Jochen (Frontiers in Human Neuroscience)
Whereas initial findings have already identified cortical patterns accompanying proprioceptive deficiencies in patients after anterior cruciate ligament reconstruction (ACLR), little is known about compensatory sensorimotor mechanisms for re-establishing postural control. Therefore, the aim of the present study was to explore leg dependent patterns of cortical contributions to postural control in patients 6 weeks following ACLR. A total of 12 patients after ACLR (25.1 ± 3.2 years, 178.1 ± 9.7 cm, 77.5 ± 14.4 kg) and another 12 gender, age, and activity matched healthy controls participated in this study. All subjects performed 10 × 30 s. single leg stances on each leg, equipped with 64-channel mobile electroencephalography (EEG). Postural stability was quantified by area of sway and sway velocity. Estimations of the weighted phase lag index were conducted as a cortical measure of functional connectivity. The findings showed significant group × leg interactions for increased functional connectivity in the anterior cruciate ligament (ACL) injured leg, predominantly including fronto−parietal [ F (1, 22) = 8.41, p ≤ 0.008, η 2 = 0.28], fronto−occipital [ F (1, 22) = 4.43, p ≤ 0.047, η 2 = 0.17], parieto−motor [ F (1, 22) = 10.30, p ≤ 0.004, η 2 = 0.32], occipito−motor [ F (1, 22) = 5.21, p ≤ 0.032, η 2 = 0.19], and occipito−parietal [ F (1, 22) = 4.60, p ≤ 0.043, η 2 = 0.17] intra−hemispherical connections in the contralateral hemisphere and occipito−motor [ F (1, 22) = 7.33, p ≤ 0.013, η 2 = 0.25] on the ipsilateral hemisphere to the injured leg. Higher functional connectivity in patients after ACLR, attained by increased emphasis of functional connections incorporating the somatosensory and visual areas, may serve as a compensatory mechanism to control postural stability of the injured leg in the early phase of rehabilitation. These preliminary results may help to develop new neurophysiological assessments for detecting functional deficiencies after ACLR in the future.
Keywords: Behavioral Neuroscience; Biological Psychiatry; Psychiatry and Mental health; Neurology; Neuropsychology and Physiological Psychology

Stance leg and surface stability modulate cortical activity during human single leg stance - Büchel, Daniel; Lehmann, Tim; Ullrich, Sarah; Cockcroft, John; Louw, Quinette; Baumeister, Jochen (Experimental Brain Research)
Abstract Mobile Electroencephalography (EEG) provides insights into cortical contributions to postural control. Although changes in theta (4–8 Hz) and alpha frequency power (8–12 Hz) were shown to reflect attentional and sensorimotor processing during balance tasks, information about the effect of stance leg on cortical processing related to postural control is lacking. Therefore, the aim was to examine patterns of cortical activity during single-leg stance with varying surface stability. EEG and force plate data from 21 healthy males (22.43 ± 2.23 years) was recorded during unipedal stance (left/right) on a stable and unstable surface. Using source-space analysis, power spectral density was analyzed in the theta, alpha-1 (8–10 Hz) and alpha-2 (10–12 Hz) frequency bands. Repeated measures ANOVA with the factors leg and surface stability revealed significant interaction effects in the left ( p = 0.045, η p 2 = 0.13) and right motor clusters ( F = 16.156; p = 0.001, η p 2 = 0.41). Furthermore, significant main effects for surface stability were observed for the fronto-central cluster (theta), left and right motor (alpha-1), as well as for the right parieto-occipital cluster (alpha-1/alpha-2). Leg dependent changes in alpha-2 power may indicate lateralized patterns of cortical processing in motor areas during single-leg stance. Future studies may therefore consider lateralized patterns of cortical activity for the interpretation of postural deficiencies in unilateral lower limb injuries.
Keywords: General Neuroscience

EEG‑derived brain graphs are reliable measures for exploring exercise‑induced changes in brain networks - Büchel, Daniel; Lehmann, Tim; Sandbakk, Øyvind; Baumeister, Jochen (Scientific Reports)
Keywords: Multidisciplinary

Pre-seasonal Assessment and Performance Diagnostics: Orthopaedic and Functional Aspects - Gokeler, Alli; Büchel, Daniel (Injury and Health Risk Management in Sports)

Modulations of Inter-Hemispherical Phase Coupling in Human Single Leg Stance - Lehmann, Tim; Büchel, Daniel; Cockcroft, John; Louw, Quinette; Baumeister, Jochen (Neuroscience)
Keywords: General Neuroscience

Effect of playing position and time on-court on activity profiles in german elite team handball - Büchel, Daniel; Jakobsmeyer, Rasmus; Döring, Michael; Adams, Michael; Rückert, Ulrich; Baumeister, Jochen (International Journal of Performance Analysis in Sport)

Phase Coupling of Bilateral Motor Areas Decreases from Bipedal to Single Leg Stance - Lehmann, Tim; Büchel, Daniel; Cockcroft, John; Abegail Louw, Quinette; Baumeister, Jochen

Exploring Functional Brain Connectivity of Postural Control in Upright Stance - Lehmann, Tim; Büchel, Daniel; Baumeister, Jochen

Effect of Cognitive Dual Task on Cortical Activation during Static Postural Control - Büchel, Daniel; Lehmann, Tim; Cockcroft, John; Abegail Louw, Quinette; Baumeister, Jochen